المسؤولية الاجتماعية للشركات كآلية لدعم الاقتصاد التضامني وتحقيق التنمية المستدامة-دراسة تحليلية للتجربة الامريكية- - جديدي, روضة; بنين, وفاء (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة الى تسليط الضوء على المسؤولية الاجتماعية للشركات ومدى قدرتها على دعم الاقتصاد التضامني الذي يمثل توجه اقتصادي تراعى فيه العدالة وتكافؤ الفرص والتكافل الاجتماعي بكل صوره. وتوصلت الدراسة الى ان الشركات تسعى في تطبيقها لبرامج المسؤولية الاجتماعية الى دعم الاعتبارات الاجتماعية والبيئية مع العمليات الاقتصادية وهو ما يساهم في تحقيق التنمية المستدامة وتحسين جودة الحياة وتقوية العلاقة مع المجتمعات وبالتالي فهي شكل من اشكال دعم الاقتصاد التضامني. This study aims to shed light on corporate social responsibility and its ability to support the solidarity economy, which represents an economic orientation in which justice, equal opportunities and social solidarity in all its forms are taken into account. The study concluded that companies, in their application of social responsibility programs, seek to support social and environmental considerations with economic operations, which contributes to achieving sustainable development, improving the quality of life and strengthening the relationship with communities, and thus it is a form of support for the solidarity economy.
Corporate social responsibility as a mechanism to support the solidarity economy An analytical study of the experiences of united state
مقال
Keywords: مسؤولية اجتماعية؛ اقتصاد تضامني؛ التنمية المستدامة ؛ شركة ميكروسفت ؛التجربة الامريكية; social responsibility, Solidarity Economy, sustainable development, Microsoft Corporation, The American experience